Creative actualization : a meliorist theory of values - McDonald, H. P. (Value Inquiry Book Series, 2011)
This book presents a major new value theory, value as creative actualization. The book takes a radically new approach to values. All potential values, whether artistic, scientific, political, or economic must be creatively actualized in the world. The theory argues for an active view in which value involves creation of novelties and thereby changes the world in some respect. Thus value is neither transcendent nor subjective, as a good of some sort has emerged in the world. Moreover, creative actualization means we can actualize standards, ideals, kinds and other norms. Creative actualization thereby dissolves the distinction between idealism and realism, since value changes the "real" with novel goods. The ideal is made real by creative actualization. The book examines traditional issues such as inherent value, modes, and meaning in the light of value as creative actualization. The later part of the book critically evaluates the history of value theory, arguing that it is insensitive to the environment and inconsistent with inherent values. Creative actualization extends historical pragmatism in novel ways. This value theory includes an ecocentric ethic, tying value theory to debates in environmental philosophy. The theory attempts to take the environment into consideration in ethics.